Evaluating the effectiveness of Moral Reconation Therapy with the juvenile offender population - Behrens, Courtney (2009)
This study aimed to evaluate the effectiveness of Moral Reconation Therapy (MRT) with the juvenile offender population in regard to the effects on recidivism. The analyses resulted in no significant differences in recidivism between the treatment group, which consisted of 375 juvenile offenders who participated in MRT, and the comparison group, which consisted of 375 juvenile offenders who did not participate in MRT. Specific attention to the number of MRT steps completed in relation to recidivism also resulted in no significant results. Therefore, recidivism did not change based on the number of MRT steps completed. In addition to analyses to determine the effectiveness of MRT, analyses to study the ability of the Juvenile Crime Prevention Risk Assessment (JCP Risk Assessment) to predict recidivism were included. Specifically, the total number of risk indicators and the total number of protective factors within the JCP Risk Assessment each were significantly related to recidivism. To determine possible moderating effects, gender and race were included for the following analyses: (a) the number of MRT steps completed and recidivism, (b) the total number of risk indicators and recidivism, and (c) the total number of protective factors and recidivism. The addition of race and gender did not provide significant results for the number of MRT steps completed and recidivism. For the JCP Risk Assessment, the interaction terms, which included race and gender separately with risk indicators and protective factors, the contribution of all independent variables, and the interaction term, led to significant variation in recidivism. However, no interaction terms accounted for a statistically significant amount of variance in recidivism. This study did not provide for support of the effectiveness of MRT with the juvenile offender population of interest